A realist interview study of a participatory public mental health project "#KindnessByPost" - Hannah Rachel Scott; Katey Warran; Kathleen Fraser; Beverley Chipp; Gail McGinnes; Mike Towers; Brynmor Lloyd-Evans; Luke Sheridan Rains (BMC, 2023)
Abstract Background #KindnessByPost (KbP) is a participatory public health initiative in which people anonymously send and receive cards containing messages of goodwill with others also taking part in the programme. Quantitative evaluations of KbP consistently find evidence of improvements to people's mental wellbeing and feelings of loneliness after participation and three months later. Our aim in the present study is to develop a programme theory of KbP, which describes for whom the KbP intervention improves mental wellbeing, other reported impacts, in which contexts it has these effects, and the mechanisms by which it works. Methods We use a realist interviewing methodology to develop the programme theory. We conducted a focus group with the KbP executive team, and 20 one-to-one interviews with KbP participants. During analysis, a co-production working group iteratively developed a Theory of Change model comprising context-mechanism-outcome statements [CMOs] to map out the mechanisms present in KbP. Results We developed 145 CMO statements, which we condensed and categorized into 32 overarching CMOs across nine thematic topics: access to scheme; pathways to involvement; resources; culture; giving post; receiving post; content of received post; community; long term impact. These CMOs set out pathways through which KbP benefited participants, including from doing something kind for someone else, of receiving post and appreciating the effort that went into it, and from the creative process of creating post and writing the messages inside them. Effects were sustained in part through people keeping the cards and through the social media communities that emerged around KbP. Discussion Both giving and receiving post and the sense of community benefited participants and improved their mood and feelings of connectedness with others. Connection with a stranger, rather than friends or family, was also an important feature of the initiative for participants. Our wide range of CMO pathways by which KbP produced positive outcomes may mean that the intervention is applicable or adaptable across many communities and settings. Taken together with evidence from the quantitative evaluations, KbP is potentially an effective, low-cost, and highly scalable public health intervention for reducing loneliness and improving wellbeing.